Efektivitas Event Marketing PT. Bintang Sayap Utama Dalam Meningkatkan Brand Awareness Rokok Red Bold di Banjarmasin - RR. Siti Munawaroh; Lydia Geonadhi; Ibrahim Daud; Afra Zainab Putri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to test and find out the effectiveness of event marketing in increasing brand awareness of Red Bold cigarettes at PT. Bintang Sayap Utama. The analysis was carried out by sampling techniques through observation and interviews. The resource persons in this study amounted to 11 people, 2 speakers from the company, and 9 direct speakers from the community. The stages of data analysis techniques are researched, namely data reduction, data presentation, and conclusions. The results showed that the ineffectiveness of PT. Bintang Sayap Utama in increasing brand awareness of Red Bold cigarettes in Banjarmasin, but has one of the advantages, namely the increase in sales volume after holding an event.